REVIEW MANUSCRIPT: A REVIEW OF SOME AFRICAN MEDICINAL PLANTS. - USUNOBUN USUNOMENA (International Journal of Pharma and Bio Sciences, 2012)
This aim of this study is to review naturally occurring dietary chemotherapeutic bioactive agents in some african medicinal plants that can be put to therapeutic use in combating inflammation and carcinogenesis without posing any deleterious effects to normal cells, tissues, organs and systems. Flavonoids possess antioxidant activity and may play a beneficial role in cancer prevention, and offer some protection against diabetes and atherosclerosis. Polyphenol prevents oxygen free radical-induced hepatocyte lethality, prevent lipopolysaccharide-induced liver injury through inhibition of inducible nitric oxide synthase and tumor necrosis factor-α expression and inhibits carcinogen or toxin-induced liver oxidative DNA damage. Acetogenins have cytotoxic properties against tumor cell lines. Cardiac glycosides helps in the treatment of congestive heart failure. Tannins exert antimicrobial activities by iron deprivation, hydrogen bounding or specific interactions with vital proteins such as enzymes in microbial cells. Terpenoid have hepatoprotective effects in albino rats.